1999
DOI: 10.1080/095851999340611
|View full text |Cite
|
Sign up to set email alerts
|

Co-ordination and control of human resource management in multinational firms: the case of CASHCO

Abstract: Much of the existing literature on the co-ordination and control of HRM in MNEs is written from the perspective of the `view from above' that often ignores or plays down the politics and changing nature of the relationships between the centre and its subsidiaries. In this paper, we take a `view from below' in exploring the politics of change in CASHCO, a well-known US MNE. The case study documents the motivation and ability of a UK subsidiary of CASHCO to respond positively to the centralized control of HRM th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 25 publications
2
30
0
2
Order By: Relevance
“…This negotiation of interests has, as noted, been a long-observed element in relations between MNC head offices and subsidiaries (for example , Brooke 1984;Martin and Beaumont 1999). But it was now being fuelled by objective structural changes, such as the growth of non-US markets and the trends described by writers such as Bartlett and Ghoshal (1998) and Hedlund (1986) toward a greater worldwide diffusion of strategic responsibilities within MNCs.…”
Section: The Negotiation Of the Centralization-autonomy Balancementioning
confidence: 99%
“…This negotiation of interests has, as noted, been a long-observed element in relations between MNC head offices and subsidiaries (for example , Brooke 1984;Martin and Beaumont 1999). But it was now being fuelled by objective structural changes, such as the growth of non-US markets and the trends described by writers such as Bartlett and Ghoshal (1998) and Hedlund (1986) toward a greater worldwide diffusion of strategic responsibilities within MNCs.…”
Section: The Negotiation Of the Centralization-autonomy Balancementioning
confidence: 99%
“…These have revealed the important role that power relations and micro-political processes play in determining the use and effectiveness of different HRM control mechanisms over time (Martin & Beaumont, 1999;Ferner, 2000). They have contributed a more dynamic view of HRM standardisation by demonstrating that standardisation, centralisation in particular, should be seen as being subjected to continual negotiation between parent and subsidiary, and is thus better viewed as comprising contested processes of 'oscillation' between greater global integration and greater local responsiveness Ferner, Almond, & Colling, 2005;Sippola & Smale, 2007).…”
Section: The Role Of Timementioning
confidence: 99%
“…For example, are these international mechanisms used more extensively to foster greater integration of compensation systems than training and development practices? A handful of authors have provided evidence to suggest that some individual HRM practices are more prone to international integration, while others are more likely to be more context bound and therefore more locally adapted (Rosenzweig and Nohria, 1994;Morley et al, 1996;Lu and Björkman, 1997;Martin and Beaumont, 1999;Tayeb, 1998;Ferner et al, 2011;Smale et al, 2013). Studies suggest that pay and benefit systems and performance appraisal systems, along with broader institutionalised aspects of the employment relations system, appear more integrated than the other HRM practices and thus local management experiences lessdecision making autonomy over these matters (Rosenzweig and Nohria, 1994;Martin and Beaumont 1999;Tayeb, 1998;Almond et al, 2005).…”
Section: Variation Of Their Usage Across Hrm Practicesmentioning
confidence: 99%
“…A handful of authors have provided evidence to suggest that some individual HRM practices are more prone to international integration, while others are more likely to be more context bound and therefore more locally adapted (Rosenzweig and Nohria, 1994;Morley et al, 1996;Lu and Björkman, 1997;Martin and Beaumont, 1999;Tayeb, 1998;Ferner et al, 2011;Smale et al, 2013). Studies suggest that pay and benefit systems and performance appraisal systems, along with broader institutionalised aspects of the employment relations system, appear more integrated than the other HRM practices and thus local management experiences lessdecision making autonomy over these matters (Rosenzweig and Nohria, 1994;Martin and Beaumont 1999;Tayeb, 1998;Almond et al, 2005). Equally, Lu and Björkman (1997) found that financial compensation, performance assessment and promotion were the most integrated within the MNC, while Ferner et al (2011) found that issues related to performance management such as the performance appraisal systems, variable pay systems or succession plans are generally more likely to be integrated internationally and therefore, controlled by HQ, while training and development, employee involvement and industrial relations practices are normally adapted locally in order to conform to the host institutional environment.…”
Section: Variation Of Their Usage Across Hrm Practicesmentioning
confidence: 99%